Esterification reaction of free fatty acid in used cooking oil using sulfonated hypercrosslinked exchange resin as catalyst - Nurul Asmawati, Roslan; Sumaiya, Zainal Abidin; Norhayati, Abdullah; Osazuwa, Osarieme Uyi; Ruwaida, Abdul Rasid; Nursofia, Mohd Yunus (Elsevier Ltd, 2021)
The production of valuable fatty acid alkyl ester (FAAE) commercially known as biodiesel from used cooking oil (UCO) as feedstock has recently gained global interest. To carry out this production process, an esterification reaction is necessary to minimize the amount of free fatty acid (FFA) in the UCO. The purpose of this research work is to evaluate the performance of the newly snythesized sulfonated hypercrosslinked exchange resin (SHER) for the esterification reaction. The catalyst was first synthesized and characterized using various physicochemical analyses (i.e. Fourier transform infra-red (FTIR), surface morphology, N2 physisorption analysis and thermogravimetric analysis (TGA)) and further subjected to the esterification reaction to determine the reaction kinetics. The esterification reaction was conducted at various catalyst loading (1−8 wt%), reaction temperatures (40−60 ◦C), and methanol to oil molar ratios (6:1−24:1). From the characterization study, SHER was found to have high decomposition temperature (up to 398 ◦C) and specific surface area (836 m2 g−1). Additionally, SHER had the capability to accommodate high number of active sites which could benefit the esterification reaction. The highest FFA conversion of 97% was achieved at 5 wt% catalyst loading, 60 ◦C of reaction temperature and 12:1 methanol to oil mole ratio in 2 h reaction time. Analyses of the spent catalyst revealed the presence of impurities residue on the SHER’s surface following the esterification reaction, and the catalyst pore remained evident even after several reusability cycles. Finally, the Eley-Rideal, pseudo-homogeneous and Langmuir-Hinshelwood-Hougen-Watson kinetic models were proposed. Due to its high activation energy; i.e. 48.4 kJ mol−1, the reaction was found to be limited by surface reaction and governed by the chemical step.